2014
DOI: 10.4414/smw.2014.14036
|View full text |Cite
|
Sign up to set email alerts
|

Childhood asthma: causes, risks, and protective factors; a role of innate immunity

Abstract: Childhood asthma is an umbrella of multifactorial diseases with similar clinical features such as mast cell and eosinophil infiltration causing airway hyper responsiveness, inflammation, and airway obstruction. There are various factors that are implicated in childhood asthma pathogenesis. A combined contribution of genetic predisposition, environmental insults, and epigenetic changes account for polarisation of the immune system towards T helper (Th) type 2 cell responses that include production of pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
74
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 118 publications
1
74
1
4
Order By: Relevance
“…Although breastfeeding has been reported to be protective against allergic diseases [2123], we found that breastfeeding for more than one month revealed an insignificantly lower OR of protection from AS (0.618) or AR (0.868) in children from non-atopic parents. This result is similar to a recent cohort study from Copenhagen Prospective Study on Asthma which showed that breastfeeding does not protect against allergic sensitization in early childhood and allergy-associated disease at age 7 years [24].…”
Section: Discussioncontrasting
confidence: 71%
“…Although breastfeeding has been reported to be protective against allergic diseases [2123], we found that breastfeeding for more than one month revealed an insignificantly lower OR of protection from AS (0.618) or AR (0.868) in children from non-atopic parents. This result is similar to a recent cohort study from Copenhagen Prospective Study on Asthma which showed that breastfeeding does not protect against allergic sensitization in early childhood and allergy-associated disease at age 7 years [24].…”
Section: Discussioncontrasting
confidence: 71%
“…17 Segundo uma pesquisa de coorte realizada na cidade de São Leopoldo, 36% das crianças asmáticas investigadas receberam aleitamento materno exclusivo por 4 meses ou mais e apenas 11% receberam-no por 6 ou mais meses. 18 O possível efeito protetor do leito materno reside no fato de que ele contém constituintes antiinflamatórios e imunomodulatórios, como lactoferrina, anticorpos imunoglobulina M (IgM), imunoglubilina G (IgG), imunoglobulina A (IgA), macrófagos, neutrófilos, linfócitos B e C e fatores de crescimento que protegem contra sensibilização alérgica durante o período de aleitamento e por pouco tempo depois do final do mesmo.…”
Section: Discussionunclassified
“…18 O possível efeito protetor do leito materno reside no fato de que ele contém constituintes antiinflamatórios e imunomodulatórios, como lactoferrina, anticorpos imunoglobulina M (IgM), imunoglubilina G (IgG), imunoglobulina A (IgA), macrófagos, neutrófilos, linfócitos B e C e fatores de crescimento que protegem contra sensibilização alérgica durante o período de aleitamento e por pouco tempo depois do final do mesmo. 17 Em relação ao diagnóstico médico de rinite e/ou eczema foi encontrado um predomínio de 43,6% em nosso estudo, sendo esta a quarta variável mais significante pela análise fatorial para caracterização do grupo estudado. Em um trabalho feito com crianças de 6 e 7 anos asmáticas foi observada uma prevalência de 38% com rinite e 11% com eczema, sendo esses achados considerados fatores associados à asma, o que corrobora com os dados encontrados em nosso estudo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Furthermore, studies have reported a positive association between both maternal infectious disease and oxidative stress during pregnancy with asthma development in the offspring. 35 …”
Section: Discussionmentioning
confidence: 99%